The Prevalence and Motivation of Cigarette Smoking among Kerman high school students - Alireza Zarezadeh; Manzumeh S Meymandi; Hassan Ziaaddini (Iranian Journal of Psychiatry, 2007)
Objective: Nicotine dependence has been identified as a critical health problem. This study assesses the prevalence and motivation of smoking among Iranian junior and senior students. Methods: A cross sectional study was performed using a questionnaire. In addition to data on frequency, motivation, initiation and cessation, this questionnaire included Fagerstrom items for nicotine dependency. The census method was used for sampling. Thus, the questionnaire was distributed to all high school junior and senior students of Kerman. Results: 3072 students participated in the study. Among them, 4.9% were nicotine dependent, 6.4% had used it occasionally during the last six months and 11.5% had used it at least once in their life. Out of all the cigarette users, 80.6% had experienced smoking before the age of 15 with 9.09±8.52 cigarette per day. Boys smoked significantly more than girls. More than 38% of the students had a history of smoking cessation. The most common motivations for smoking among the students have been identified as smoking of the peer group and the belief that smoking is fashionable. Conclusions: The motivation and gender difference in smoking were similar to the general population. The rate of nicotine dependency was less than other parts of the country. However, the age of smoking initiation was in a decreasing trend and similar to other parts of the country. High school stage is a very critical period for adolescents' smoking. Therefore, for the provision of more social skills trainings and behavioral therapies, providing information for decision makers is recommended.